(untitled) (Research, Society and Development, 2020)
The aims of the research are to find out what contribution Abdur Rozak Fachruddin has made in Islamic education. This study used a qualitative method. The approach is a historical one. Meanwhile, the search of data source uses two methods, namely documentation and literature. There are two sources of data, primary and secondary. In this research, Primary data is referenced through books written by him and books written by others that discussing the figure. Meanwhile, secondary data is supporting data. The results of the study concluded that Abdur Rozak Fachruddin has contributed to Islamic education, especially to Muhamamdiyah School of Education in Indonesia. The efforts were made such as revoking the ban on veiling for Islamic students in public schools, being Muhammadiyah teachers, providing courses for Hizbul Wathon development, and helping establishment of Muhammadiyah University in Yogyakarta.